Fabrication of submicrosized imprinted spheres attached polypropylene membrane using "two-dimensional" molecular imprinting method for targeted separation. Issue 1 (March 2017) - Meng, Minjia; Feng, Yonghai; Liu, Yan; Dai, Xiaohui; Pan, Jianming; Yan, Yongsheng
The submicrosized imprinted polypropylene microfiltration membrane (SIPM) for salicylic acid (SA) was prepared by water-in-oil emulsion polymerization method and two-dimensional imprinting method based on polypropylene microfiltration membrane with salicylic acid as template molecule, 4-vinyl pyridine as functional monomer, Span 80 as emulsifier, toluene as the oil phase, ethyleneglycol dimethacrylate as cross-linking agent, and 2, 2′-azobis (2-methylpropionitrile) as initiator. The structure, morphology, and surface wettability of SIPM were characterized by Raman spectra, contact angle, and scanning electron microscopy. Flux test shows that the submicrosized imprinted spheres on the membrane is beneficial for increasing the membrane flux. Static adsorption experiment indicates that SIPM has a selective rebinding for salicylic acid. Moreover, the adsorption amount of salicylic acid over SIPM increased with properly increasing the amount of imprinted spheres on the SIPM. Permeation experiment shows that transport mechanism for permeation of the salicylic acid and acetylsalicylic acid toward SIPM is accordance with the facilitated mechanism.